Políticas públicas de incentivo à leitura: o Programa Nacional Biblioteca da Escola (PNBE) no câmpus Paraíso do Tocantins do Instituto Federal do Tocantins - Soares, Ustana Ferraz (Universidade Federal do Tocantins, 2019)
The collection of the National School Library Program in the process of mediation and literary reading at the high school of the Federal Institute of Tocantins with emphasis on Campus Paraíso do Tocantins. The problem that prompts this research is the public policy that offers materiality to cultural assets and the difficulties encountered in the circulation process and the effective use of the acquis in the school environment. The research is based on the study of reading conceptions, international public policies for books, reading and libraries, especially in Latin America, and the history of government initiatives to encourage reading in Brazilian society. Practical readings in Brazil are identified from the results of the International Student Assessment Program, the Brazilian Literacy Indicator, the National Continuous Household Sample Survey, and the Portraits of Reading research in Brazil. The National School Library Program is presented as a policy of distribution of literary and didactic collections to the public school libraries in order to supply the lack of cultural goods. The methodology includes qualitative research assumptions with a case study design. Data were collected through documentary sources from the Ministry of Education and Federal Institute of Tocantins, semi-structured interviews and questionnaire. It was based on the design of Content Analysis of Bardin (1977) for the analysis of the data. The locus of the research is Campus Paraíso do Tocantins and the subjects investigated include the librarians of the Federal Institute of Tocantins, teachers of Portuguese and foreign languages and the students of the integrated high school of Campus Paraíso do Tocantins. Above all, it is based on ethical elements of research based on Resolution 196 (BRASIL, 1996a). The constructed data make it possible to answer the following question: how has the school community appropriated the collections made available by the National School Library Program to stimulate reading? The results indicate that the National School Library Program collection did not contribute to the promotion of effective reading practices. It was observed that the mediators do not perform reading activities with the works of the collection, however, the students have the teachers as responsible for the formation of the reader. It was found that 49.25% of the students disagree with the methodologies and didactics applied in literature classes and 80.6% use the library for purposes other than reading and borrowing books. The profile of the readers was identified: most of the students read (62.68%) and liked literature (70.90%), mainly, books that portray their daily life; 52.24% do not read because of school requirements and 50% read printed books. In relation to professionals, they are readers guided by professional and learning issues. It was found that the National School Library Program is maintained as a distributive policy and not a training of readers, since it is necessary for the mediators to appropriate the collection to bring them closer to the students. It is intended, therefore, to contribute to critical reflections on public reading policies.